Middle English texts in transition : a festschrift dedicated to Toshiyuki Takamiya on his 70th birthday - Horobin, Simon; Mooney, Linne; Graham, Timothy (Manuscript culture in the British Isles., 2014)
Fresh contributions to the study of medieval manuscripts, texts, and their creators.